Legal Problems Related to Mineral and Coal Mining Permits - Abdillah Dalimunte; Mohammad Ghufron AZ; Supriyadi Supriyadi (Jurnal Cakrawala Hukum, 2023)
The issues that will be discussed in this research include what are the legal implications of transferring the authority to issue mining permits after the latest publication and what are the regulations regarding mining permits after mining permits are issued. The purpose of this study is to provide a review of legal changes related to the Mineral and Coal Mining Law. This study uses normative legal research methods with several approaches, namely the statutory approach and the conceptual approach. As a result of the transfer of the issuance of mining permits to the central government, it appears that this is aimed at unraveling licensing issues which will later facilitate the investment climate in Indonesia so as to increase Indonesia's economic growth. The impact that occurs is the authority owned by the local government where currently the local government does not have attributive authority in terms of issuing mining permits. Harmonization of Mining Business Permit arrangements means seeking conformity or harmony between laws and regulations so that overlapping regulations do not occur and as a process of establishing laws and regulations to address conflicting matters among the legal norms that have been in effect.How to cite item: Dalimunte, Abdillah, Mohammad Gufron AZ, Supriyadi, â€œLegal Problems Related to Mineral and Coal Mining Permits.â€ Jurnal Cakrawala Hukum 14 no. 1 (2023): 76-85. DOI: 10.26905/idjch.v14i1.9872.